Capacity design criteria for seismic resistance of precast concrete columns using steel box connection - Chayanon Hansapinyo (2018)
© Int. J. of GEOMATE. A variety of advantages of precast concrete adding to benefits of concrete has made the pre-fabrication and assembly systems widely adopted in building construction business. However, the connections may diminish the increase in the utilization due to their complication in the installation work and seismic design consideration. This paper presents an easy-to-install steel box for column base connection designed based on the standard capacity design criteria. Experimental investigations on the precast concrete columns using the steel box connection at the column base under cyclic loading were also made. The test results show the satisfactory seismic performance of the precast specimens both in seismic shear capacity, ductility and energy dissipation compared with the identical cast-in-place specimen. The failure of the precast columns, with proper details, was in the flexural ductile mode. The shear capacity was respectively 1.16-1.24 times higher than the averaged capacity of the cast-in-place column. The damping ratio was about 18-25 percent in the inelastic range, after the drift ratio of 3.0%. Finally, the seismic performance of the designed precast concrete column using the steel box connection based on the capacity design criteria is guaranteed without early brittle failures.